Preparation method of self-repairing super-hydrophobic fabric
The fabric surface is modified by hydroxyl-terminated PDMS/boric acid and micro-nanoparticle finishing solution, and self-healing is achieved by dynamic crosslinking of B-O bonds, which solves the problem of poor durability of existing superhydrophobic coatings and improves the superhydrophobic performance recovery ability of the fabric surface .
Patent Information
- Application Number
- CN202411592034.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The existing superhydrophobic coatings are difficult to repair after mechanical damage, resulting in poor durability.
The fabric surface is modified by hydroxy-terminated PDMS/boric acid and micro-nanoparticle finishing solution, and a rough structure is constructed and a dynamic crosslinked B-O bond between boric acid and hydroxy-terminated PDMS is used to achieve self-healing.
The durability of superhydrophobic properties after mechanical damage is improved, ensuring that the fabric surface can restore superhydrophobic properties after damage.
Smart Images

Figure CN119465649A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a method for preparing a self-repairing super-hydrophobic fabric. Background Art
[0002] Inspired by lotus leaves, gecko feet and other plants and animals in nature, people have successfully prepared a series of bionic super-hydrophobic surfaces. Due to their special wetting properties, they are widely used in waterproofing, anti-fouling, anti-corrosion, anti-icing, anti-oil, oil-water separation and other fields. Low surface energy materials and rough structures are two key factors in constructing super-hydrophobic surfaces. Therefore, researchers have studied a variety of methods for preparing super-hydrophobic surfaces from these two perspectives, such as sol-gel method, hydrothermal method, electrochemical corrosion method, vapor deposition method, phase separation method, etc. However, these methods have the disadvantages of long molding cycle and small molding area, which are difficult for large-scale production; and the super-hydrophobic interface prepared by them has poor mechanical and chemical stability, poor bonding between the substrate and the modified material, and a large amount of organic solvents and fluorine-containing substances are used in the preparation process. These factors have severely limited their practical application.
[0003] In recent years, people usually prepare super-hydrophobic fabrics by first depositing micro-nanoparticles on the surface of the fabric to construct a rough structure, and then modifying the surface with fluorinated polymers to reduce the surface energy; however, these often rely on physical adsorption, have weak binding force, and are easily affected by mechanical damage. In practical applications, these super-hydrophobic coatings are difficult to repair after mechanical damage, so how to solve the problem of the durability of super-hydrophobic coatings is still a major challenge. Summary of the invention
[0004] In view of the technical problem that the existing super-hydrophobic surface is difficult to repair after being damaged, the present invention provides a method for preparing a self-repairing super-hydrophobic fabric, wherein the surface of the fabric is modified by a hydroxyl-terminated PDMS / boric acid / micro-nano particle finishing liquid, the micro-nano particles construct a rough structure to give the surface super-hydrophobic properties, and after the surface is damaged, the BO bonds dynamically cross-linked between boric acid and hydroxyl-terminated PDMS are used to restore the super-hydrophobic properties of the fabric surface, so that the super-hydrophobic properties have good durability.
[0005] To achieve the above objectives, the present invention adopts the following technical scheme: a method for preparing a self-repairing super-hydrophobic fabric, comprising the following steps:
[0006] (1) Preparation of finishing liquid: dissolving boric acid in isopropanol to form a boric acid solution, adding hydroxyl-terminated polydimethylsiloxane to the boric acid solution under first heating, stirring to obtain a mixed solution, then stirring under second heating to evaporate the mixed solution until the volume of the mixed solution is reduced to half of the original volume, and then dispersing micro-nano particles in the mixed solution to obtain a finishing liquid;
[0007] (2) Preparation of self-repairing super-hydrophobic fabric: The cleaned fabric is placed in the finishing solution obtained in step (1), and after immersion, the fabric is taken out and dried to obtain a self-repairing super-hydrophobic fabric.
[0008] Furthermore, in step (1), the dissolution is ultrasonic dissolution, the time of the ultrasonic dissolution is 15 to 30 minutes, and the temperature is 25 to 35°C.
[0009] Furthermore, in step (1), the first heating is water bath heating, the water bath heating temperature is 60-75° C.; the stirring is magnetic stirring, the rotation speed of the magnetic stirring is 250 rpm.
[0010] Furthermore, in step (1), the second heating is oil bath heating, and the temperature of the oil bath heating is 95-105°C.
[0011] Furthermore, in step (1), the amount of boric acid used is 5-25% of the mass of hydroxyl-terminated polydimethylsiloxane; the micro-nano particles are silicon dioxide micro-nano particles, titanium dioxide micro-nano particles, zinc oxide micro-nano particles or aluminum oxide micro-nano particles; the amount of the micro-nano particles used is 1-10% of the mass of polydimethylsiloxane.
[0012] Furthermore, in step (2), the cleaning treatment is to place the fabric in acetone and anhydrous ethanol solutions respectively, ultrasonically clean the fabric to remove wax and impurities on the surface, and then take it out and dry it; the ultrasonic cleaning time is 10 to 60 minutes, the drying temperature is 50 to 100° C., and the drying time is 1 to 24 hours.
[0013] Furthermore, in step (2), the mass ratio of the finishing liquid to the fabric is 1 to 5:1; the immersion time is 2 to 20 minutes; the drying temperature is 50 to 120° C., and the drying time is 10 to 24 hours.
[0014] A self-repairing super-hydrophobic fabric is obtained by the above preparation method.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) Polydimethylsiloxane (PDMS) has good chemical stability, good water resistance and wear resistance, excellent waterproof performance and good adhesion performance. Methyl-terminated PDMS is a commonly used adhesive for preparing fluorine-free super-hydrophobic coatings. The present invention uses hydroxyl-terminated PDMS, which is dynamically cross-linked with boric acid at a certain temperature to form BO bonds, thereby having self-repairing properties, so its durability is better. The adhesion performance of hydroxyl-terminated PDMS can also be used to ultrasonically disperse micro-nano particles to construct a rough structure, thereby preparing a self-repairing super-hydrophobic fabric.
[0017] (2) Through a simple one-step impregnation method, the hydroxyl-terminated PDMS / boric acid solution can not only modify the surface of the fabric through a strong binding force, but also evenly penetrate into the interior of the fiber, so as to construct a micro-nano structure on the surface of the fabric and disperse the low surface energy hydrophobic substance hydroxyl-terminated PDMS / boric acid into the interior of the fabric; the surface of the hydroxyl-terminated PDMS / boric acid / X@fabric (X is SiO2 micro-nano particles, TiO2 micro-nano particles, Al2O3 micro-nano particles or ZnO micro-nano particles) shows a rougher micro-nano structure and exhibits more excellent super-hydrophobic properties. In addition, no fluorine-containing substances are used in the preparation process, the raw materials are non-toxic and green, the preparation method is simple, the controllability is good, and it is suitable for large-scale and industrial production;
[0018] (3) The BO bonds produced by the reaction of boric acid and hydroxyl-terminated PDMS are evenly modified on the surface of the fabric. Even after multiple washing and friction tests, the contact angle is still large, the hydrophobicity is maintained well, and excellent mechanical stability is exhibited. Although the hydroxyl-terminated PDMS / boric acid / X@fabric (X is SiO2 micro-nanoparticles, TiO2 micro-nanoparticles, Al2O3 micro-nanoparticles or ZnO micro-nanoparticles) will be damaged by washing or friction during use, after being placed or heated for a period of time, the super-hydrophobic properties will be restored due to the dynamically cross-linked BO bonds. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a preparation flow chart of Example 1;
[0020] Figure 2 The result diagram of the water contact angle of the fabric prepared by adding different amounts of silicon dioxide micro-nano particles in Example 1;
[0021] Figure 3 This is the SEM image of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric of Example 1;
[0022] Figure 4 This is the EDS spectrum of hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric of Example 1;
[0023] Figure 5 (a) FTIR and (b) XPS graphs of unmodified cotton fabric and hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric of Example 1;
[0024] Figure 6 The process diagram of (a) damage and (b) self-repair of the composite film after knife cutting experiment in Example 1;
[0025] Figure 7A bar graph showing the time required for self-repairing of a membrane prepared by hydroxyl-terminated PDMS / boric acid / SiO2 in Example 1 and a membrane prepared by hydroxyl-terminated PDMS / boric acid without dispersed SiO2 at different temperatures;
[0026] Figure 8 The contact angle change diagram of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric after 100 friction-self-repairing times in Example 1;
[0027] Fig. 9 FTIR images of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric of Example 1 before abrasion, after abrasion and after self-repair;
[0028] Fig.10 (a) XPS full spectrum and (b) Si2p narrow spectrum of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric of Example 1 before wear, after wear and after self-repair;
[0029] Fig.11 This is a contact angle change diagram of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric of Example 1 after 10 washings;
[0030] Fig.12 This is an optical image of the contact angle of the wool fabric of hydroxyl-terminated PDMS / boric acid / SiO2 in surface modification example 1;
[0031] Fig.13 The oil-water separation process of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric prepared in Example 1 is (a) an optical image of the original oil-water mixture, (b) an optical image of the oil-water separation process, and (c) an optical image of the upper layer of the methylene blue aqueous solution and the lower layer of the oil solution after oil-water separation. DETAILED DESCRIPTION
[0032] In order to clearly illustrate the technical features of this solution, this solution is described below through a specific implementation method.
[0033] The present invention provides a method for preparing a multifunctional, durable and self-repairing super-hydrophobic fabric surface, which specifically comprises the following steps:
[0034] (1) Preparation of a hydroxyl-terminated PDMS / boric acid / X (X is SiO2 micro-nano particles, TiO2 micro-nano particles, Al2O3 micro-nano particles or ZnO micro-nano particles) finishing solution: firstly, dissolving boric acid in isopropanol by ultrasonication to form an isopropanol solution of boric acid, then adding the hydroxyl-terminated PDMS to the isopropanol solution of boric acid under heating in a water bath, stirring magnetically to obtain a mixed solution, then evaporating the mixed solution in an oil bath until the volume of the mixed solution is reduced to half of the original volume, then ultrasonically dispersing the micro-nano particles in the mixed solution to obtain a finishing solution;
[0035] (2) Preparation of self-repairing super-hydrophobic fabric: first, place the fabric in acetone and anhydrous ethanol solutions respectively, ultrasonically clean to remove wax and impurities on the surface, and then take it out and dry it; then place the fabric in the finishing liquid prepared in step (1), take it out and dry it after immersion to obtain a self-repairing super-hydrophobic fabric.
[0036] In step (1), the ultrasonic time is 15 to 30 minutes, the temperature is 25 to 35° C.; the temperature of the water bath heating is 60 to 75° C., the temperature of the oil bath is 90 to 110° C., and the speed of the magnetic stirring is 250 rpm.
[0037] In step (1), the amount of boric acid used is 5-25wt% of the mass of the hydroxyl-terminated polydimethylsilane; the micro-nano particles are silicon dioxide micro-nano particles, titanium dioxide micro-nano particles, zinc oxide micro-nano particles or aluminum oxide micro-nano particles, and the amount of the micro-nano particles used is 1-10wt% of the mass of the hydroxyl-terminated polydimethylsiloxane.
[0038] In step (2), the ultrasonic cleaning time is 10 to 60 minutes, and the drying temperature is 50 to 100° C. for 1 to 24 hours.
[0039] In step (2), the mass ratio of the finishing liquid to the fabric is 1 to 5:1, the immersion time in the finishing liquid is 2 to 20 minutes, and the drying temperature of the hydroxyl-terminated PDMS / boric acid / X@ fabric is 50 to 120° C. for 10 to 24 hours.
[0040] The self-healing super-hydrophobic fabric was tested for wear resistance, water washing and chemical stability in harsh environments: after the hydroxyl-terminated PDMS / boric acid / X@ fabric was damaged by mechanical force, it became hydrophilic. It can be restored to super-hydrophobic properties by placing it in an oven to dry for a period of time, or leaving it to stand for a period of time indoors; the number of friction times is 10 to 200 times, and the number of water washing times is 1 to 10 times; the drying temperature in the oven is 50 to 120°C, and the time is 1 to 10 hours; the temperature of the indoor standing temperature is 10 to 35°C, and the time is 10 to 24 hours.
[0041] The hydroxyl-terminated PDMS / boric acid / X@ fabric was used for oil-water separation test: the superhydrophobic fabric was fixed on the oil-water separator, dichloroethane (oil) and deionized water dyed blue with methylene blue were mixed, and the oil-water mixture was poured into the oil-water separator for separation. The number of oil-water separations was 1 to 50 times.
[0042] Example 1
[0043] The self-repairing super-hydrophobic fabric of this embodiment is obtained by the following steps:
[0044] (1) Boric acid in an amount of 6.7% of the mass of hydroxyl-terminated PDMS was weighed and ultrasonically dissolved in 6 mL of isopropanol, 2 mL of hydroxyl-terminated PDMS was added, and magnetic stirring was performed at 75° C. in a water bath for 30 min to obtain a mixed solution, and then magnetic stirring was performed in an oil bath at 110° C. to evaporate the mixed solution until the volume of the mixed solution was reduced to half of the original volume, and then 3% of the mass of hydroxyl-terminated PDMS was ultrasonically dispersed uniformly in the mixed solution to obtain a hydroxyl-terminated PDMS / boric acid / SiO2 finishing solution;
[0045] (2) The cotton fabric was first cut into 3×3 cm squares, placed in acetone and anhydrous ethanol solutions for ultrasonic cleaning respectively, taken out after 30 minutes, and dried in an oven at 60°C for 12 hours; then, the hydroxyl-terminated PDMS / boric acid / SiO2 finishing solution was weighed to make the mass ratio of the hydroxyl-terminated PDMS / boric acid / SiO2 finishing solution to the cotton fabric be 2:1, the cotton fabric was placed in the finishing solution, immersed for 5 minutes, then taken out, and dried in an oven at 110°C for 17 hours to obtain a self-healing superhydrophobic cotton fabric.
[0046] The surface of the self-repairing super-hydrophobic cotton fabric prepared in Example 1 was analyzed, and the measured water contact angle was 159.3°.
[0047] Figure 1 The preparation flow chart of Example 1 is shown. A hydroxyl-terminated PDMS / boric acid / SiO2 finishing solution is first prepared, and a super-hydrophobic fabric is prepared by a one-step impregnation method. PDMS and boric acid are complexed to produce dynamic covalent bonds that can self-repair. During the ultrasonic dispersion process, a portion of SiO2 micro-nanoparticles are grafted with PDMS, which can enhance the bonding force with the fabric and enhance the surface roughness, thereby improving the super-hydrophobicity of the fabric. The super-hydrophobic fabric is prepared by the impregnation method only because hydrogen bonding can be generated between the finishing solution and the fabric, and can be easily and large-scale attached to the fabric.
[0048] Figure 2 The change of water contact angle of fabrics prepared by adding different amounts of silicon dioxide micro-nano particles in Example 1 is shown. When the amount is 3%, the hydrophobic property is optimal.
[0049] Figure 3 This is the SEM image of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric of Example 1. It can be seen from the figure that after the cotton fabric is immersed in a finishing solution of boric acid, hydroxyl-terminated PDMS and silica and dried, the surface of the cotton fabric has a multi-scale rough structure composed of micro-nano scale protrusions and pits, forming many micro-nano nipple structures, which greatly increases the surface roughness and improves the hydrophobic properties of the cotton fabric, with a contact angle of up to 159.3°.
[0050] Figure 4This is the EDS spectrum of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric of Example 1. It can be seen that since the main components of the hydroxyl-terminated PDMS are C, Si, and O elements, and the B element of boric acid are evenly distributed, this indicates that the hydroxyl-terminated PDMS / boric acid / SiO2 layer is successfully loaded on the surface of the cotton fabric.
[0051] Figure 5 (a) FTIR and (b) XPS images of unmodified cotton fabric and hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric. Compared with the original cotton fabric, the modified cotton fabric with hydroxyl-terminated PDMS / boric acid / SiO2 has a higher carbon content at 1335 cm -1 The BO bond peak appears at 1258 cm, indicating that PDMS and boric acid have successfully achieved network chain exchange and formed dynamic cross-linking bonds. -1 The representative peak of the asymmetric stretching vibration of Si-O bond appears at 792cm -1 The Si-C bond representative peak and the C1s spectrum in XPS all indicate that the PDMS / boric acid / SiO2 layer is well grafted on the entire cotton fabric. In addition, the original cotton fabric in the XPS graph is composed of only carbon and oxygen elements, and two new Si 2p and 2s representative peaks appear at 101.0eV and 153.0eV in the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric, indicating that the cotton fabric is completely encapsulated by the PDMS / boric acid / SiO2 layer.
[0052] Figure 6 The diagram shows the process of (a) damage and (b) self-repair of the hydroxyl-terminated PDMS / boric acid / SiO2 composite membrane of Example 1 after a knife cutting experiment. The composite membrane is formed by pouring the hydroxyl-terminated PDMS / boric acid / SiO2 finishing liquid of Example 1 into a mold and directly curing it. The composite membrane damaged by knife cutting can be accelerated to recover at high temperature and can be restored in about 30 minutes at 110°C.
[0053] Figure 7 The hydroxyl-terminated PDMS / boric acid / SiO2 composite film prepared in Example 1 and the PDMS / boric acid film without dispersed SiO2 were subjected to knife cutting experiments at the same time. The time bar graph required for self-repair at different temperatures, as shown in the figure, found that the composite film with SiO2 micro-nano particles recovered to its original state at any temperature in a shorter time. It is inferred that the addition of micro-nano particles can not only improve the super-hydrophobic performance, but also improve the self-repair effect. This may be due to the change in the thermodynamic properties of the composite film after the addition of micro-nano particles, which accelerates the transition of the composite film from a gel state to a liquid state. This elastic behavior makes the super-hydrophobic coating have good resistance to external mechanical damage.
[0054] Figure 8The contact angle change diagram of 100 times of friction-self-repair of hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric prepared in Example 1. The obtained super-hydrophobic fabric was subjected to an experiment of contact friction with sandpaper. After 20 times of sandpaper wear, the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric lost its super-hydrophobicity, and the water contact angle dropped to 108.6°. However, when the worn cotton fabric was heated at 60°C for 30 minutes, it regained its super-hydrophobicity, and the water contact angle was 157.7°. As the number of wear and heating cycles increased, the water contact angle decreased slightly. After 100 times of sandpaper friction, the surface of the cotton fabric was severely worn and almost became hydrophilic, but after heating at 110° for 30 minutes, the super-hydrophobicity was restored, and the contact angle was still higher than 150°. In addition, the self-repair process of the super-hydrophobic coating can also be carried out at room temperature, but it takes nearly 1 day. This may be due to the low surface energy components hydroxyl-terminated PDMS / boric acid present inside the cotton fibers being released to the fabric surface after heat treatment or long-term storage, thus restoring the superhydrophobicity.
[0055] Fig. 9 The FTIR images of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric prepared in Example 1 before, after and after self-repair. From the FTIR image, it can be seen that the peak intensity of the BO bond after wear becomes weaker, and the peak of the -OH exposed on the surface is enhanced. The BO part is broken, but it is easy to dynamically cross-link to achieve self-repair performance, and the infrared peak intensity is re-enhanced, which verifies the dynamic cross-linking of the BO bond and thus has self-repair performance. During the impregnation process, a large number of hydroxyl-terminated PDMS molecules penetrate into the amorphous region of the cellulose macromolecule along with the water molecules. After the water evaporates, the hydrophobic component remains inside the cotton fiber. After the surface of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric is mechanically damaged, the super-hydrophobic performance fails, and the continuous mechanical wear causes the BO bond to be unable to cross-link and recover in time, thereby destroying the rough structure composed of the coated silica micro-nanoparticles, resulting in a decrease in super-hydrophobic performance. This phenomenon may be due to the fact that the damaged hydroxyl-terminated PDMS / boric acid layer on the surface of the cotton fabric recovers its superhydrophobicity through dynamically cross-linked BO bonds after heating or long-term storage. It may also be due to the fact that the hydroxyl-terminated PDMS / boric acid components stored inside the cotton fibers migrate outward after heating or long-term storage, and re-constitute a rough structure coated with silica micro-nanoparticles.
[0056] Fig.10(a) XPS full spectrum and (b) Si2p narrow spectrum of hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric before wear, after wear and after self-repair prepared in Example 1. XPS test was performed on the surface chemical composition of hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric before wear, after wear and after heat treatment. The characteristic peak of Si 2p at 101.0 eV weakened after wear, but increased after heat treatment and self-repair, which further verified this phenomenon.
[0057] Fig.11 The contact angle change diagram of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric prepared in Example 1 after 10 washings. The obtained super-hydrophobic cotton fabric was washed 10 times according to the GB / T 3921-2008 standard. The hydrophobicity of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric did not decrease significantly, the contact angle remained above 150°, and the water droplets could still maintain a spherical shape. The long cycle washing time only caused a slight change, indicating that the super-hydrophobic hydroxyl-terminated PDMS / boric acid / SiO2 layer has a high mechanical stability.
[0058] Fig.12 To obtain the contact angle optical image of the wool fabric of the hydroxyl-terminated PDMS / boric acid / SiO2 surface modification example 1, the hydroxyl-terminated PDMS / boric acid / SiO2 finishing solution prepared in step (1) of example 1 was used to prepare hydroxyl-terminated PDMS / boric acid / SiO2@wool fabric according to step (2) of example 1. Fig.12 As can be seen in the figure, the spherical water droplets are maintained, which can intuitively demonstrate the superhydrophobic properties of hydroxyl-terminated PDMS / boric acid / SiO2@wool fabric.
[0059] Fig.13 The oil-water separation process of the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric prepared in Example 1 is sequentially (a) optical image of the original oil-water mixture, (b) optical image of the oil-water separation process, and (c) optical image of the upper layer of the methylene blue aqueous solution and the lower layer of the oil solution after the oil-water separation. The hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric is fixed on the oil-water separator, 50mL of deionized water dyed blue by methylene blue and 50mL of dichloroethane (oil) are mixed together, and the oil-water mixture is poured into the oil-water separator for separation. The oil permeates the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric, and the water is blocked on the hydroxyl-terminated PDMS / boric acid / SiO2@cotton fabric, and the oil and water are successfully separated.
[0060] Example 2
[0061] The self-repairing super-hydrophobic fabric of this embodiment is obtained by the following steps:
[0062] (1) Boric acid in an amount of 5% of the mass of hydroxyl-terminated PDMS was weighed and ultrasonically dissolved in 6 mL of isopropanol, 2 mL of hydroxyl-terminated PDMS was added, and magnetic stirring was performed at 75° C. in a water bath for 30 min to obtain a mixed solution, and then magnetic stirring was performed in an oil bath at 110° C. to evaporate the mixed solution until the volume of the mixed solution was reduced to half of the original volume, and then titanium dioxide micro-nanoparticles in an amount of 1% of the mass of the hydroxyl-terminated PDMS were ultrasonically dispersed uniformly in the mixed solution to obtain a hydroxyl-terminated PDMS / boric acid / TiO2 finishing solution;
[0063] (2) The polyester fabric was first cut into 3×3 cm squares, and ultrasonically cleaned in acetone and anhydrous ethanol solutions respectively. The squares were taken out after 30 min and dried in an oven at 60 °C for 12 h. Then, the hydroxyl-terminated PDMS / boric acid / TiO2 finishing solution was weighed to make the mass ratio of the hydroxyl-terminated PDMS / boric acid / TiO2 finishing solution to the polyester fabric be 2:1. The polyester fabric was placed in the finishing solution, immersed for 5 min, and then taken out and dried in an oven at 110 °C for 17 h to obtain a self-healing superhydrophobic polyester fabric.
[0064] The surface of the self-repairing super-hydrophobic fabric prepared in Example 2 was analyzed, and its contact angle was measured to be about 155.3°.
[0065] Example 3
[0066] The self-repairing super-hydrophobic fabric of this embodiment is obtained by the following steps:
[0067] (1) Boric acid in an amount of 10% of the mass of hydroxyl-terminated PDMS was weighed and ultrasonically dissolved in 6 mL of isopropanol, 2 mL of hydroxyl-terminated PDMS was added, and magnetic stirring was performed for 30 min in a water bath at 75° C. to obtain a mixed solution, and then magnetic stirring was performed in an oil bath at 110° C. to evaporate the mixed solution until the volume of the mixed solution was reduced to half of the original volume, and then aluminum oxide micro-nanoparticles in an amount of 2% of the mass of the hydroxyl-terminated PDMS were ultrasonically dispersed uniformly in the mixed solution to obtain a hydroxyl-terminated PDMS / boric acid / Al2O3 finishing solution;
[0068] (2) The wool fabric was first cut into 3×3 cm squares, and ultrasonically cleaned in acetone and anhydrous ethanol solutions respectively. The squares were taken out after 30 min and dried in an oven at 60 °C for 12 h. Then, the hydroxyl-terminated PDMS / boric acid / Al2O3 finishing solution was weighed to make the mass ratio of the hydroxyl-terminated PDMS / boric acid / Al2O3 finishing solution to the wool fabric be 2:1. The wool fabric was placed in the finishing solution, immersed for 5 min, then taken out, and dried in an oven at 110 °C for 17 h to obtain a self-healing superhydrophobic wool fabric.
[0069] The surface of the self-repairing super-hydrophobic fabric prepared in Example 3 was analyzed, and its contact angle was measured to be about 156.1°.
[0070] Example 4
[0071] The self-repairing super-hydrophobic fabric of this embodiment is obtained by the following steps:
[0072] (1) Boric acid in an amount of 15% of the mass of hydroxyl-terminated PDMS was weighed and ultrasonically dissolved in 6 mL of isopropanol, 2 mL of hydroxyl-terminated PDMS was added, and magnetic stirring was performed at 75° C. in a water bath for 30 min to obtain a mixed solution, and then magnetic stirring was performed in an oil bath at 110° C. to evaporate the mixed solution until the volume of the mixed solution was reduced to half of the original volume, and then zinc oxide micro-nanoparticles in an amount of 4% of the mass of the hydroxyl-terminated PDMS were ultrasonically dispersed uniformly in the mixed solution to obtain a hydroxyl-terminated PDMS / boric acid / ZnO finishing solution;
[0073] (2) The polyamide fabric was first cut into 3×3 cm squares, placed in acetone and anhydrous ethanol solutions for ultrasonic cleaning respectively, taken out after 30 minutes, and dried in an oven at 60°C for 12 hours; then, the hydroxyl-terminated PDMS / boric acid / ZnO finishing solution was weighed to make the mass ratio of the hydroxyl-terminated PDMS / boric acid / ZnO finishing solution to the polyamide fabric be 2:1, the polyamide fabric was placed in the finishing solution, immersed for 5 minutes, taken out, and dried in an oven at 110°C for 17 hours to obtain a self-healing superhydrophobic polyamide fabric.
[0074] The surface of the self-repairing super-hydrophobic fabric prepared in Example 4 was analyzed, and its contact angle was measured to be about 153.7°.
Claims
1. A method for preparing a self-repairing super-hydrophobic fabric, characterized in that: The following steps are involved: (1) Preparation of finishing liquid: dissolving boric acid in isopropanol to form a boric acid solution, adding hydroxyl-terminated polydimethylsiloxane to the boric acid solution under first heating, stirring to obtain a mixed solution, then stirring under second heating to evaporate the mixed solution until the volume of the mixed solution is reduced to half of the original volume, and then dispersing micro-nano particles in the mixed solution to obtain a finishing liquid; (2) Preparation of self-repairing super-hydrophobic fabric: The cleaned fabric is placed in the finishing solution obtained in step (1), and after immersion, the fabric is taken out and dried to obtain a self-repairing super-hydrophobic fabric.
2. The preparation method according to claim 1, characterized in that: In step (1), the dissolution is ultrasonic dissolution, the time of the ultrasonic dissolution is 15 to 30 minutes, and the temperature is 25 to 35°C.
3. The preparation method according to claim 1, characterized in that: In step (1), the first heating is water bath heating, the water bath heating temperature is 60-75° C.; the stirring is magnetic stirring, the rotation speed of the magnetic stirring is 250 rpm.
4. The preparation method according to claim 1, characterized in that: In step (1), the second heating is oil bath heating, and the temperature of the oil bath heating is 95-105°C.
5. The preparation method according to claim 1, characterized in that: In step (1), the amount of boric acid used is 5-25% of the mass of hydroxyl-terminated polydimethylsiloxane; the micro-nano particles are silicon dioxide micro-nano particles, titanium dioxide micro-nano particles, zinc oxide micro-nano particles or aluminum oxide micro-nano particles; the amount of the micro-nano particles used is 1-10% of the mass of polydimethylsiloxane.
6. The preparation method according to claim 1, characterized in that: In step (2), the cleaning treatment is to place the fabric in acetone and anhydrous ethanol solutions respectively, ultrasonically clean the fabric to remove wax and impurities on the surface, and then take it out for drying; the ultrasonic cleaning time is 10 to 60 minutes, the drying temperature is 50 to 100° C., and the drying time is 1 to 24 hours.
7. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the finishing liquid to the fabric is 1 to 5:1; the immersion time is 2 to 20 minutes; the drying temperature is 50 to 120° C., and the drying time is 10 to 24 hours.
8. A self-repairing super-hydrophobic fabric, characterized in that: The method is obtained by any one of claims 1 to 7.
Citation Information
Patent Citations
Low-temperature self-repairing conductive material based on reversible boron-oxygen bond
CN112480586A
Super-hydrophobic cotton fabric with self-healing function and preparation method thereof
CN118498074A